The Link between Attachment Style and Conflict Resolution Strategies in Romantic Relationships - Hasan, Zulkifli; Ridzky, Tengku; Riau, Ahmad (Journal Social Humanity Perspective, 2025)
In the current study, the connection between attachment styles and conflict resolution strategy in romantic relations is explored, and the results are placed in the context of the greater management literature. Although attachment theory has a long history of explaining individual variation in regulating emotions and interpersonal relations, little is known about how this theory applies to conflict management in organizational contexts. Based on a quantitative research design, a sample of adult participants was used to measure the levels of attachment orientations, including secure, anxious, and avoidant attachment, as well as the predictive relationship between these variables and constructive and destructive conflict management models. Inferential statistical tests; correlations, ANOVA and regression identified that secure attachment had positive relationship with integrative and constructive conflict strategy, while anxious attachment was positively related to escalation strategy and destructive strategy, and avoidant attachment was positively related to withdrawal strategy and disengagement strategy. Such results are not limited in intimate relationships but contribute to understanding how the dispositional orientations influence conflict management behaviors that individuals also apply to work-related situations. The results prove the relevance of recognizing attachment-sensitive tendencies in management, leadership and team work. To organizations, the research has practical implications: training and human resource development programs should target not only situational conflict antecedents, but also underlying dispositional orientations that affect behavior. Moreover, the research also demands reconstructing conflict competence as a process of psychological security and organizational arrangements that lead to trust and relation safety. The present study can be considered as an extension of the conflict management literature by providing a bridge between the psychological understanding and use in management. It highlights that the emotional structure of human relationships, which is based on attachment, continues to be the key to individual and organizational achievement.